Recommended metrics for quantifying underwater noise impacts on North Atlantic right whales. (February 2022) - Marotte, Emmaline; Wright, Andrew J.; Breeze, Heather; Wingfield, Jessica; Matthews, Leanna P.; Risch, Denise; Merchant, Nathan D.; Barclay, David; Evers, Clair; Lawson, Jack; Lesage, Veronique; Moors-Murphy, Hilary; et al.
Abstract: Anthropogenic underwater noise has been identified as a potentially serious stressor for the critically endangered North Atlantic right whale (NARW). The Government of Canada is undertaking steps to better characterize the noise sources of most concern and their associated impacts, but there is currently an insufficient understanding of which noise sources are most impacting NARW in their Canadian habitat. This knowledge gap together with the myriad possible methods and metrics for quantifying underwater noise presents a confounding and challenging problem that risks delaying timely mitigation. This study presents the results from a 2020 workshop aimed at developing a series of metrics recommended specifically for better characterizing the types of noise deemed of greatest concern for NARW in Canadian waters. The recommendations provide a basis for more targeted research on noise impacts and set the stage for more effective management and protection of NARW, with potential conservation applications to similar species. Highlights: We present the first recommended metrics for assessing noise impacts on North Atlantic right whales in Canadian waters. The types and characteristics of noise of most concern to North Atlantic right whales in Canadian waters are identified. Recommendations were informed by the expertise of a diverse set of researchers and professionals in various fields. Metrics to best quantify physiological and behavioural impacts from noise are discussed and recommended. Recommendations will support targeted research efforts to better understand noise impacts on North Atlantic right whales.